Acoustic Energy Harvesting using Dual Piezoelectric Plates - Bin Tarsh, Maleka AbdulBari (2017)
A Master of Science thesis in Mechatronics Engineering by Maleka AbdulBari Bin Tarsh entitled, "Acoustic Energy Harvesting using Dual Piezoelectric Plates," submitted in May 2017. Thesis advisor is Dr. Jin-Hyuk Lee. Soft and hard copy available.